Treatment of extranodal NK/T-cell lymphoma: From past to future - Yan, Zheng; Yao, Shuna; Wang, Zhizhong; Zhou, Wenping; Yao, Zhihua; Liu, Yanyan (Frontiers in Immunology, 2023)
Extranodal NK/T-cell lymphoma (ENKTCL) is the most common subtype of T/NK-cell lymphoma in Asia and Latin America, but very rare in North American and Europe. Patient survival has improved significantly over the past two decades. However, standard treatment has not yet been established, although dozens of prospective trials have been conducted. To help understand how the treatment of ENKTCL has evolved in the past and what trends lie ahead, we have comprehensively reviewed the treatment of this aggressive malignancy, with a particular focus on neglected or unanswered issues, such as the optimal staging method, the best partner of asparaginase (Asp), the individualized administration of Asp, the preferred sequence of CT and RT and so on. Overall, the 5-year overall survival (OS) of patients with Ann Arbor stage I/II disease increased from < 50% in the early 20th century to > 80% in recent years, and the median OS of patients with Ann Arbor stage III/IV disease increased from < 1 year to more than 3 years. The improvement in patient survival is largely attributable to advances in radiation technology and the introduction of Asp and anti-PD-1/PD-L1 immunotherapy into practice. Radiotherapy is essential for patients with early-stage disease, while Asp-based chemotherapy (CT) and PD-1/PD-L1 inhibitors significantly improved the prognosis of patients with advanced-stage disease. ENKTCL management is trending toward simpler regimens, less toxicity, and higher efficacy. Novel drugs, such as manufactured T cells, monoclonal antibodies, and small molecule inhibitors, are being intensively investigated. Based on the fact that ENKTCL is highly resistant to cytotoxic drugs except Asp, and aggressive CT leads to higher toxicity rather than better outcomes, we recommend it is unnecessary to expend additional resources to compare different combinations of Asp with cytotoxic agents. Instead, more efforts should be made to optimize the use of Asp and immunotherapy to maximize efficacy and minimize toxicity, explore ways to overcome resistance to Asp and immunotherapy, identify novel treatment targets, and define subpopulations who may benefit more from specific treatments.